Effect of Temperature and Gamma Radiation on Salmonella Hadar Biofilm Production on Different Food Contact Surfaces - Najla Ben Miloud Yahia; Salma Kloula Ben Ghorbal; Lobna Maalej; Abdelwaheb Chatti; Alya Elmay; Nour-Eddine Chihib; Ahmed Landoulsi (Journal of Food Quality)
Salmonella is a pathogen transmitted by foods and it is one of the most important target bacteria in food irradiation studies. Few works were carried out on the effectiveness of gamma radiation against biofilms formed by this bacterium. Salmonella can form a biofilm on different material surfaces. The physicochemical properties of surfaces and environmental factors influence the adhesion of this pathogen. The present study investigated the effect of gamma radiation (1 and 2 kGy) and temperature (28°C and 37°C) on the development of Salmonella Hadar biofilm on polyvinyl chloride (PVC), glass, cellophane paper (CELLO), and polystyrene (POLY). The obtained results indicated that biofilm production is surface and temperature dependent. In addition, biofilm formation decreased significantly after gamma irradiation at either 1 or 2 kGy doses. However, the agfD and adrA genes expression did not demonstrate significant decrease. This work highlighted that gamma radiation treatment could reduce the biofilm formation of Salmonella enterica serovar Hadar on different food contact surfaces.